2020
DOI: 10.3390/su12208305
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Wider Longitudinal Road Markings on Vehicle Speeds in Two-Lane Rural Highways

Abstract: Longitudinal road markings are a valuable aid in driving guidance. An increase in their width may influence driving and, therefore, road safety. Wider road markings generate a perception of a narrowing lane, which may induct drivers to reduce speed. The present study tries to verify if an increased width of longitudinal road markings actually helps one to drive more slowly, and consequently leads to enhanced road safety. For this purpose, three curves with reduced visibility were selected and driving speed was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…It is found that the visibility of the white pavement markings is better than that of the yellow markings under the same conditions; the visibility of the pavement marking with a width of 20 cm is better than that of the marking with a width of 15 cm. Wider markings are better for visual recognition, which is similar to previous research in a driving simulator [ 11 , 12 , 13 , 14 , 15 ]. The driver sees the color of the pavement markings in relation to the color of the light reflected from the markings.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It is found that the visibility of the white pavement markings is better than that of the yellow markings under the same conditions; the visibility of the pavement marking with a width of 20 cm is better than that of the marking with a width of 15 cm. Wider markings are better for visual recognition, which is similar to previous research in a driving simulator [ 11 , 12 , 13 , 14 , 15 ]. The driver sees the color of the pavement markings in relation to the color of the light reflected from the markings.…”
Section: Discussionsupporting
confidence: 86%
“…Manual on Uniform Traffic Control Devices for Streets and Highways (MUTCD) describes that changes in the color and width of longitudinal pavement markings affect the driver’s ability to perceive roadway contours [ 9 ]. Calvo-Poyo, F. et al found that wider road markings have a speed-reducing effect by a study of the influence of the width of the longitudinal road markings on the speed of circulation [ 11 ]. Park, E. S. et al studied the safety effect of wider edge lines by analyzing crash frequency data for road segments with and without wider edge lines, and the results showed that wider edge lines are effective in reducing crashes on rural, two-lane highways [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the initial fuzzy decision matrix was defined on the basis of the scale shown in Table 9. Taking into account the given linguistic scale, the initial fuzzy decision matrix was formed, after which Equations ( 14) and (15) were applied in order to determine ideal and anti-ideal solutions. The extended fuzzy initial matrix is shown in Table 10, and it is important to note that criteria C1, C2, and C4 are beneficial and thus for whom the maximum value is desired, while the others belong to the group of cost criteria with the preference of the minimum value.…”
Section: Application Of the Fuzzy Marcos Methods In Order To Make Final Ranking Of Road Sectionsmentioning
confidence: 99%
“…The use of wider longitudinal road markings leads to a reduction in the speed of vehicles, and thus a reduction in the number of traffic accidents. The analysis of speed reduction in day and night driving conditions at average traffic volume showed the following reduction in vehicle speed: 2.24% during the day and 1.96% at night for light vehicles, and 2.46% during the day and 2.15% at night for heavy vehicles [15]. Using the Bayesian network analysis for predicting the probability of the influence of traffic and road factors on the occurrence of traffic accidents, it is especially emphasized that vehicle speed, horizontal curve radius, vehicle type, adhesion coefficient, and longitudinal slope are important factors [11].…”
Section: Literature Reviewmentioning
confidence: 98%
“…Colonna proposed that safety principles need to be accurately followed when carrying out road geometric design [22]. Calvo found that wide signs are more effective at reducing speed on weekends and when there is heavy traffic [23]. In addition to the above research, traffic safety management policies have also attracted scholars' attention [24,25].…”
Section: Introductionmentioning
confidence: 99%